The impact of overall obesity on serotonin level in the acute phase of coronavirus infection and post-coronavirus sequelae: aspects of neuropsychological and cognitive impairments - Zinych, O. V.; Kushnarova, N. M.; Shuprovych, A. A.; Trofymenko, O. M. (Zaporozhye Medical Journal, 2023)
Aim: to study the relationship between neurotransmitter support and the degree of cognitive and psycho-emotional impairments in patients in the post-coronavirus period depending on the presence of overall obesity. Materials and methods. 44 patients aged 19 to 76 years (17 women and 27 men) with a history of moderate-to-severe COVID-19 were examined. 2 groups were allocated depending on body mass index (BMI): Group 1 – 20 non-obese patients (BMI <30 kg/m2; male / female 10/10); Group 2 – 24 obese people (BMI ≥30 kg/m2; male / female 17/7). The groups of subjects were comparable in age, length of hospital stay, severity of COVID-19, hematological and biochemical parameters, C-reactive protein, D-dimer. Parameters of quality of life (QL), psycho-emotional state, and cognitive function were studied by a questionnaire method 6 months after recovery. Results. It has been found that the serotonin level was significantly lower in the acute period of infection in the group of obese patients compared to that in the non-obese group. However, after treatment, serum serotonin returned to reference values. No significant differences were detected between the two groups of patients regarding the values of neurocognitive and social parameters in the post-COVID period. Correlation analysis has shown that QL scores in Group 1 were positively correlated with cognitive function (r from 0.54 to 0.73) and negatively – with anxiety and depression (r from -0.60 to -0.80). In Group 2, the serotonin level was positively correlated with self-assessments of the QL (r from 0.42 to 0.53) and negatively – with cognitive abilities and anxiety (r from -0.51 to -0.60). Conclusions. The presence of obesity (BMI ≥30 kg/m2) in patients with COVID-19 was accompanied by reduced serum serotonin levels during the acute phase of COVID-19. In the post-COVID period, the initial level of serotonin in obese patients was correlated with the deterioration of quality of life and worsening cognitive function assessments.